Descriptive Analysis of Social Media Usage and Gender in Generation Z Investment Interest in Sukabumi - Ratri Pramudita; Dea Arme Tiara Harahap (Rescollacom (Research Collaborations Community), 2026)
This study aims to provide a descriptive overview of social media usage patterns, gender differences, and tendencies in investment interest among young generations. The research employs a descriptive quantitative method involving 100 respondents who completed an online questionnaire. The research instrument consists of closed-ended Likert-scale questions and open-ended questions analyzed using thematic analysis. The results indicate that the majority of respondents show a positive tendency toward investment, as reflected by the high percentage of agreement and strong agreement with statements related to investment interest. Social media, particularly TikTok and Instagram, appears to play a significant role as an information source that facilitates access and stimulates initial interest in investment. Descriptively, female respondents tend to demonstrate more cautious behavior and a long-term orientation, while male respondents are more likely to exhibit confidence and a greater willingness to take risks. The thematic analysis of open-ended responses reveals that the primary motivations for investing focus on future planning, financial stability, and profit opportunities. Overall, this study provides a comprehensive picture of investment interest and behavior patterns based on social media characteristics and gender. These findings may serve as a foundation for further associative or inferential research.